Determination of Standard Parameters and Phytochemical Screening of Ethanol Extract of Burdock Root (Arctium lappa L.) - Aliifah, Maitsa Wafaa; Nurdianti, Lusi; Wildan Muhtar, Mohammad; Arif Maulana Yusuf, Fitra; Octavia, Tasya; Nur Fadilah, Yayang (Universitas Padjadjaran (Unpad), 2023)
Gobo root (Arctium lappa L.) is one plant that is empirically used to lower blood sugar levels. The phytochemical content and standard parameters of Gobo root ethanol extract were investigated in this study. The maceration method was used to extract the samples using 70% ethanol solvent. The thick extract was obtained by evaporation. The percentage yield of gobo root extract (Arctium lappa L.) obtained was 46.24%. The results of organoleptic (macroscopic) examination produce blackish-brown extracts, thick, slightly sour taste, and a distinctive smell. Furthermore, phytochemical screening tests were carried out and determination of extract standard parameters which included water-soluble pollen, ethanol-soluble juice, drying shrinkage, water content, and total ash content. Obtained chemical compounds from gobo root extract, namely alkaloids, flavonoids, tannins, polyphenols, and triterpenoids. The results of determining the standard parameters of gobo root extract showed the value of water soluble juice content of 84.55% and ethanol soluble juice content of 27.8%.The drying shrinkage value is 25.52%, the moisture content is 5%, and the total ash content is 0.41%.Keywords: Arctium lappa L., Extract standardization, Phytochemical screening, Maseration extraction